Relationship between the biomass of reef shark and fish in South Morotai Waters, North Maluku, Indonesia (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Sofyan JF, Ambariyanto A, Suwartimah K, Toha AHA. 2020. Relationship between the biomass of reef shark and fish in South Morotai Waters, North Maluku, Indonesia. Biodiversitas 21: 5605-5613. This study aims to determine the biomass of reef shark and fish in South Morotai Waters in North Maluku, Indonesia. The Audible Stationary Count and Underwater Visual Census method were used to collect the data of reef sharks and fish. Seven and one site locations of coral reef and shark ecosystems were surveyed and, the data were analyzed using regression analysis to obtain a correlation between the variables. The three reef sharks found were Carcharhinus melanopterus, Triaenodon obesus, and Carcharhinus amblyrhynchos. Biomass estimation of reef sharks and fish ranged from 0.59 to 19.97 kg/ha and 30.95 kg/ha to 49.92 kg/ha, consisting of 8 families. In the area of aggregations, both species were found in 7 sites, and the population of reef shark amounted to 86.96 kg/ha and fish was around 55.705 kg/ha, consisting of 9 families. There was a positive relationship between the biomass of reef shark and fish in South Morotai waters, and the index of determination was 0.8043, showing that the biomass of reef shark was influenced by that of fish. These results indicated the importance of biomass in determining the functional composition and diversity of reef shark and fish.
Keywords: Audible stationary count, biomass, correlation, reef fish, reef shark, South Morotai